Deposit insurance and impact on the financial system - Maté, Martina (Oeconomica Jadertina, 2018)
The importance of financial system stability is best demonstrated by the recent global financial crisis. The slump in the financial markets and institutional disturbances have threatened seriously the financial systems around the world and questioned their role in mediating the exchange of capital surplus and their targeting to deficit entities. Many financial institutions have found themselves on the verge of collapse, and countries around the world have launched expansionary measures and invested huge resources in rescuing their markets. As financial and banking crises always cause fiscal pressure, the importance of upgrading the financial system through preventive measures that will preserve public confidence in its security and protect the economy from major losses is surely in the interest of governments worldwide. The goal of these measures, referred to as the financial system security grids, is to create controlled conditions for less informed market participants and protect them from loss. Deposit insurance systems have been recognized as one of the key elements of the financial system preventive security grids. The most important goal of the organized deposit insurance system is to protect the assets of so-called “small savers” or consumers unable to independently assess the risk of the institution in which they relocate their surplus funds. The aim of this paper is to explain the role of an organized deposit insurance system with special attention to the system in the Republic of Croatia.
Keywords: financial system stability; financial crisis; financial institutions; security measures; deposit insurance; protection of funds; The Republic of Croatia